Characteristics of Vanadium Doped And Bamboo Activated Carbon Coated LiFePO4 And Its Performance For Lithium Ion Battery Cathode - Nofrijon Sofyan; Subkhan Alfaruq; Anne Zulfia; Achmad Subhan (Balai Besar Kimia dan Kemasan, 2018)
Vanadium doped and bamboo activated carbon coated lithium iron phosphate (LiFePO4) used for lithium ion battery cathode has been successfully prepared. Lithium iron phosphate was prepared through a wet chemical method followed by a hydrothermal process from the starting materials of LiOH, NH4H2PO4, and FeSO4.7H2O. The dopant variations of 0 wt.%, 3 wt.%, 5 wt.%, and 7 wt.% of vanadium and a fixed 3 wt.% of bamboo activated carbon were carried out via a solid-state reaction process each by using NH4VO3 as a source of vanadium and carbon pyrolyzed from bamboo tree, respectively. The characterization was carried out using X-ray Diffraction (XRD) for the phase formed and its crystal structure, Scanning Electron Microscope (SEM) for the surface morphology, Electrochemical Impedance Spectroscopy (EIS) for the conductivity, and battery analyzer for the performance of lithium ion battery cathode. The XRD results show that the phase formed has an olivine based structure with an orthorhombic space group. Morphology examination revealed that the particle agglomeration decreased with the increasing level of vanadium concentrations. Conductivity test showed that the impedance of solid electrolyte interface decreased with the increase of vanadium concentration indicated by increasing conductivity of 1.25 x 10-5 S/cm, 2.02 x 10-5 S/cm, 4.37 x 10-5 S/cm, and 5.69 x 10-5 S/cm, each for 0 wt.%, 3 wt.%, 5 wt.%, and 7 wt.% vanadium, respectively. Vanadium doping and bamboo activated carbon coating are promising candidate for improving lithium ion battery cathode as the initial charge and discharge capacity at 0.5C for LiFePO4/C at 7 wt.% vanadium is in the range of 8.0 mAh/g.